A Role for the CAL1-Partner Modulo in Centromere Integrity and Accurate Chromosome Segregation in Drosophila. - Chen, C.C.; Greene, E.; Bowers, S.R.; Mellone, B.G. (PLoS ONE, 2012)
The relationship between the nucleolus and the centromere, although documented, remains one of the most elusive aspects of centromere assembly and maintenance. Here we identify the nucleolar protein, Modulo, in complex with CAL1, a factor essential for the centromeric deposition of the centromere-specific histone H3 variant, CID, in Drosophila. Notably, CAL1 localizes to both centromeres and the nucleolus. Depletion of Modulo, by RNAi, results in defective recruitment of newly-synthesized CAL1 at the centromere. Furthermore, depletion of Modulo negatively affects levels of CID at the centromere and results in chromosome missegregation. Interestingly, examination of Modulo localization during mitosis reveals it localizes to the chromosome periphery but not the centromere. Combined, the data suggest that rather than a direct regulatory role at the centromere, it is the nucleolar function of modulo which is regulating the assembly of the centromere by directing the localization of CAL1. We propose that a functional link between the nucleolus and centromere assembly exists in Drosophila, which is regulated by Modulo.